THE INFLUENCE OF TEACHERS' PEDAGOGICAL COMPETENCE ON THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN PUBLIC SENIOR HIGH SCHOOLS IN RANAH PESISIR DISTRICT - Maharani, Mutia; Ningrum, Tia Ayu; Kadri, Hanif Al; Luthfiani, Luthfiani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The background of this study is the poor implementation of the independent curriculum in public high schools in the Ranah Pesisir subdistrict. One of the factors influencing this is teacher pedagogical competence. Therefore, the main objective of this study is to determine the effect of teacher pedagogical competence on the implementation of the independent curriculum in public high schools in the Ranah Pesisir subdistrict. A quantitative approach with a correlational method was used. The research sample consists of a number of teachers selected using the Proportionate Stratified Random Sampling technique, calculated based on the Stratified Random Sampling formula. Data collection was conducted using a questionnaire with a Likert scale. The validity and reliability of the instrument were tested using statistical software, which indicated that the instrument was suitable for use in the study. The results of the data analysis indicated that the influence of teachers' pedagogical competence on the implementation of the Merdeka Curriculum at the State Senior High School in Ranah Pesisir District was in the “very good” category. Based on these findings, it is recommended that continuous training be conducted, more comprehensive observation instruments be developed, a qualitative approach be used in further research, more specific training needs be mapped, and support for facilities and infrastructure be improved to support optimal administrative performance.